Back Cover Image. Issue 5 (17th July 2020) - Safa, Bauback; Jain, Sonu; Desai, Mihir J.; Greenberg, Jeffrey A.; Niacaris, Timothy R.; Nydick, Jason A.; Leversedge, Fraser J.; Megee, David M.; Zoldos, Jozef; Rinker, Brian D.; McKee, Desirae M.; MacKay, Brendan J.; et al.
Abstract : The back cover image is based on the Original Article Peripheral Nerve Repair Throughout the Body with Processed Nerve Allografts: Results from a Large Multicenter Study by Bauback Safa, fraser leversedge, Yasser E‐sheikh et al., https://doi.org/10.1002/micr.30574 .